(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study is bound to compare the level of competency of general academic strand students in hybrid learning modalities, including face-to-face learning and online learning modalities. The objective of this study is to find out if the level of competency of general academic strand students is the same or if there is a difference in terms of the two learning modalities. In Contrast to the Hypothesis used in this study, the result of the Conducted test shows that there is no significant difference in the Level of Competency of the General Academic Strand on Hybrid Learning Modality, including Face-to-face Learning and Online Learning. The results have revealed that the General Academic Strand Students’ Level of Competency is Just the same no matter what type of Learning modality is to be used. The results of the study show that the Students of the General Academic Strand are Highly Competent in Hybrid Learning Modality.